Ictal ECG changes in temporal lobe epilepsy Alterações eletrocardiográficas ictais em epilepsia do lobo temporal - L.M. Li; J. Roche; J.W.A.S. Sander (Arquivos de Neuro-Psiquiatria)
Changes in cardiac rhythm may occur during epileptic seizures and this has been suggested as a possible mechanism for sudden unexpected death amongst patients with chronic epilepsy (SUDEP). We have studied ECG changes during 61 complex partial seizures of temporal lobe origin in 20 patients. Tachycardia was observed in 24/61 (39%) and bradycardia in 3/61 (5%). The mean and median tachycardia rate was 139 and 140 beats/min (range 120-180). The longest R-R interval observed was 9 seconds. No difference was found in regard to the lateralisation of seizures and cardiac arrhytmia. One of the patients with bradycardia was fitted with a demand cardiac pacemaker, which appeared to decrease the number of his falls. In conclusion, ictal cardiac changes which may be seen in temporal lobe epilepsy (TLE) are sinus tachycardia and occasionally sinus bradycardia. Patients presenting vague complains suggestive of either TLE or cardiac dysrhythmia, simultaneous monitoring with EEG/ECG is required, and if the episodes are frequent, video-EEG should be considered. Further studies on this subject are warranted as this may shed some light on possible mechanisms for SUDEP. Alterações no ritmo cardíaco podem ocorrer durante crises epilépticas. Estas alterações têm sido sugeridas como possível mecanismo para explicar morte súbita em pacientes com epilepsia crônica. Analisamos o eltrocardiograma (ECG) em 61 crises parciais complexas do lobo temporal de 20 pacientes. Taquicardia foi observada em 24/61 (39%) e bradicardia em 3/61 (5%). A média e a mediana da taquicardia foram 139 e 140 batimentos por minuto (variando de 120-180). O intervalo R-R mais longo foi 9 segundos. Não houve diferença em relação a lateralisação das crises e alteração do ritmo cardíaco. Um paciente com bradicardia recebeu marcapasso de demanda, com diminuição importante das suas quedas durante as crises. Em conclusão, as alterações cardíacas ictais em crises do lobo temporal mais comuns são taquicardia sinusal e menos frequentemente bradicardia. Em pacientes com queixas vagas que sugerem tanto epilepsia e arritmia cardíaca, monitorização simultânea com EEG/ECG é recomendada e se as crises forem frequentes, vídeo-EEG deve ser considerado. Estudos nesta área são necessários para esclarecimento de possíveis mecanismos da morte súbita em pacientes com epilepsia.